Optimisasi Penambahan Limbah Drilling Cutting Pada Proses Bioremediasi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
The company ways to maintain its production of crude oil, by drilling new wells and wells that have done some existing treatments. These activities will generate waste, and called with sludge drilling cutting. Characteristics of drilling cutting waste is similar to petroleum-contaminated soil. Based on the Decree of the Minister of the Environment No. 128 of 2003 on Procedures for the Technical Requirements for Waste Oil and Soil Contaminated by Petroleum Biological, waste oil is classified as hazardous and toxic waste ( B3 ) . One way to improve the quality of petroleum-contaminated soil is bioremediation techniques . In the process of bioremediation, microbes in the soil to degrade hydrocarbons that contaminate the soil. In this study drilling cutting waste is added to the oil- contaminated soil samples, which will be processed in bioremediation using naturally existing microorganisms. The results of the most effective and efficient comparison of the addition of contaminated soil and drilling cutting waste is 3:2 and its supported by the pH value of the sample in neutral pH range ( 6,5 - 7,5 ), because the hydrocarbon degrading bacteria can grow well on the pH. Â Key word: drilling cutting, TPH, bioremediasi, hidrokarbon.